The Mission Comes First: Exploring the Mechanisms of Organizational Sponsorship for the Acceleration of Social Start-Ups - Niklas Manhart (Junior Management Science (JUMS), 2022)
A significant number of incubators and accelerators have emerged to support start-ups aiming to solve societal or environmental problems. However, there is still limited understanding of how these ventures perceive the value proposition of incubators and accelerators – and whether their support needs differ from conventional start-ups. This study uses the framework of organizational sponsorship to explore the acceleration of social start-ups. It is based on in-depth interviews with the founders of 10 start-ups from an impact-oriented incubator in Duisburg, Germany. Through an inductive case study, this research generates three main insights. First, the social-mission focus of these ventures leads to significant differences as compared to commercial ventures. Second, social start-ups profit more from intangible resources such as social capital than from tangible resources such as seed funding. Third, incubators and accelerators need to adapt their offerings to address the needs of social start-ups. This study presents the first systematic assessment of incubator and accelerator services from the perspective of social start-ups. Its main theoretical contribution is to extend the organizational sponsorship framework by proposing a novel support mechanism: impact acceleration.
Keywords: 650; Business incubation; start-up accelerators; social entrepreneurship; social start-ups; organizational sponsorship